Tungsten oxide with different oxygen contents: Sliding properties - Polcar, T. (2007)
In this study, tungsten oxide coatings with 13 and 75 at% of oxygen were prepared by DC reactive magnetron sputtering from a pure W target in an Ar+O2 atmosphere. The coating hardness (H) decreased with increasing oxygen content from 25 to 7.7 GPa. The values of H/E ratio were 0.08 and 0.07 for W87O13 and W25O75, respectively.